Adsorption of Bovine Serum Albumin on Poly(vinylidene fluoride) Surfaces in the Presence of Ions: A Molecular Dynamics Simulation - Shaikh, Abdul Rajjak; Karkhanechi, Hamed; Yoshioka, Tomohisa; Matsuyama, Hideto; Takaba, Hiromitsu; Wang, Da-Ming (The Journal of Physical Chemistry B, 2018)
Adsorption of bovine serum albumin (BSA) on poly(vinylidene fluoride) (PVDF) surfaces in an aqueous environment was investigated in the presence and absence of excess ions using molecular dynamics simulations. The adsorption process involved diffusion of protein to the surface and dehydration of surface–protein interactions, followed by adsorption and denaturation. Although adsorption of BSA on PVDF surface was observed in the absence of excess ions, denaturation of BSA was not observed during the simulation (1 μs). Basic and acidic amino acids of BSA were found to be directly interacting with PVDF surface. Simulation in a 0.1 M NaCl solution showed delayed adsorption of BSA on PVDF surfaces in the presence of excess ions, with BSA not observed in close proximity to PVDF surface within 700 ns. Adsorption of Cl– on PVDF surface increased its negative charge, which repelled negatively charged BSA, thereby delaying the adsorption process. These results will be helpful for understanding membrane fouling phenomena in polymeric membranes, and fundamental advancements in these areas will lead to a new generation of membrane materials with improved antifouling properties and reduced energy demands.